Composite material and method of manufacturing composite material

A composite material with perovskite nanoparticles in a layered oxide matrix addresses the instability issue of organic polymer-based composites, offering improved durability and stability through ion-exchanged layered oxides and ligands, facilitating higher nanoparticle density and efficient manufacturing.

JP2025002500APending Publication Date: 2025-01-09UNIVERSITY OF YAMANASHI +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023102721
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-22
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Conventional composite materials using organic polymers as a matrix for perovskite nanoparticles suffer from instability due to moisture and light, leading to poor long-term stability.

Method used

A composite material is developed using a layered oxide structure as the matrix, where perovskite nanoparticles are dispersed, formed by ion-exchanging metal ions and cations in a layered oxide, and incorporating a ligand, providing improved stability.

Benefits of technology

The composite material exhibits enhanced durability against moisture and light, maintaining the stability and luminescent properties of perovskite nanoparticles, with higher nanoparticle density and simpler manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002500000001_ABST
    Figure 2025002500000001_ABST
Patent Text Reader

Abstract

To provide a novel composite material including a perovskite type nanoparticle by using a matrix of a material replacing an organic polymer.SOLUTION: A composite material of the present invention is a composite material which includes a perovskite type nanoparticle having a composition represented by general formula ABX3 and a ligand in a laminar oxide structure derived from a laminar oxide. A composite material of the present invention is obtained by forming a laminar oxide with at least some of metal ions in the laminar oxide ion-exchanged with cations B, followed by mixing the laminar oxide and a supply source of monovalent cations A and monovalent anions X, and a supply source of ligands in an organic solvent.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite material and a method for making a composite material. [Background technology]

[0002] Nanoparticles (quantum dots) of perovskite-type metal halide compounds having a composition represented by the general formula ABX3 (where A represents a monovalent cation, B represents a divalent cation, and X represents a monovalent anion) (hereinafter referred to as "perovskite-type nanoparticles" or simply "nanoparticles") exhibit excellent light absorption properties and the property of emitting light with a high quantum yield, and by changing the type and ratio of X, it is possible to obtain luminescent colors in almost the entire range of visible light from blue to red. In particular, since the full width at half maximum in the emission spectrum is narrow and the color purity is high, perovskite-type nanoparticles have attracted attention in many fields as functional materials such as luminescent materials and wavelength conversion materials.

[0003] However, perovskite nanoparticles are highly ionic and have low stability against water. For example, the crystals of the nanoparticles are prone to defects due to reactions with water molecules in the atmosphere, and physical properties such as luminescence properties and wavelength conversion properties are easily lost. Therefore, as one method for improving stability, it has been considered to disperse the nanoparticles in a polymer matrix to protect the nanoparticles from water molecules in the atmosphere (Patent Document 1 and Non-Patent Document 1).

[0004] Patent Document 1 discloses a composite luminescent material in which perovskite nanoparticles are dispersed in a polymer matrix, and the mass ratio of the perovskite nanoparticles to the matrix is ​​1: (1 to 50) (claims). The composite luminescent material of Patent Document 1 is produced, for example, by dissolving a polymer (polyvinyl acetate, cellulose acetate, polyvinylidene fluoride, etc.) in an organic solvent, sonicating the solution to prepare a first solution, dissolving an inorganic metal halide and an organic amine halide salt in an organic solvent, sonicating the solution, filtering the solution to prepare a second solution, mixing the first solution and the second solution, sonicating the solution to prepare a precursor solution, applying the precursor solution to a substrate, and drying the precursor solution (Example 1, etc.).

[0005] Non-Patent Document 1 discloses that the stability of perovskite nanoparticles (quantum dots) in water is improved by encapsulating them in a hydrophobic macroscale polymer matrix (abstract). The composite material of Non-Patent Document 1 is produced, for example, by mixing nanoparticles and a pre-synthesized polymer (such as poly(styrene-ethylene-butylene-styrene)) in toluene, sonicating the mixture to prepare a dispersion, applying the dispersion to a substrate, and drying it (pp. 35529-, "Materials and Methods"). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2018-522959 [Non-patent literature]

[0007] [Non-Patent Document 1] SN Raja, et al. ACS Applied Materials and Interfaces 2016, Vol. 8, 35523-35533 Summary of the Invention [Problem to be solved by the invention]

[0008] However, conventional techniques use organic polymers as matrices. In general, organic polymers are prone to degradation due to the effects of moisture and light in the atmosphere, and long-term stability may not be sufficient. The present inventors considered it desirable to provide a composite material containing perovskite nanoparticles that uses a material instead of organic polymers as a matrix.

[0009] The present invention has been made in view of the above problems, and has an object to provide a new composite material containing perovskite nanoparticles using a material that replaces organic polymers as a matrix.

[0010] Inorganic materials are expected to be used as matrix materials to replace organic polymers. However, when inorganic materials are used as the matrix, composite materials cannot be produced by the method adopted when organic polymers are used as the matrix, that is, by dispersing nanoparticles in a solvent in which the matrix material is dissolved, applying the dispersion, and drying the dispersion. Therefore, it is necessary to develop a new production method. Therefore, an object of the present invention is to provide a new production method for the composite material. [Means for solving the problem]

[0011] As a result of intensive research, the present inventors have found that when a metal ion in a layered oxide is ion-exchanged with a cation B, and then the layered oxide, a source of a monovalent cation A and a monovalent anion X, and a source of a ligand are mixed in a solvent, a composite material is obtained that contains perovskite-type nanoparticles having a composition represented by the general formula ABX3 and a ligand in a layered oxide structure derived from the layered oxide, and have completed the present invention.

[0012] The present invention is as follows. <1> A composite material containing perovskite nanoparticles having a composition represented by the general formula ABX3 and ligands in a layered oxide structure: Here, A represents one or more monovalent cations, B represents one or more divalent cations, X represents one or more monovalent anions, and at least a portion of the anions X are halide anions. <2> The layered oxide structure is an oxide containing at least one atom selected from silicon, boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, zinc, molybdenum, tungsten, niobium, and tantalum. <1> The composite material according to claim 1, <3> The layered oxide structure is an oxide containing silicon atoms. <2> The composite material according to claim 1, <4> At least a portion of the layered oxide structure is silicon oxide; <3> The composite material according to claim 1. <5> The halide anion is at least one selected from a chloride anion, a bromide anion, and an iodide anion; <1> ~ <4> 2. The composite material according to claim 1 . <6> At least a portion of the cations A is at least one selected from the group consisting of methylammonium cations, formamidinium cations and cesium cations; <1> ~ <5> 2. The composite material according to claim 1 . <7> At least a portion of the cations B are main group metal cations; <1> ~ <6> 2. The composite material according to claim 1 . <8> The typical metal cation is the magnesium cation (Mg 2+ ), calcium cation (Ca 2+ ), strontium cation (Sr 2+ ), barium cation (Ba 2+ ), zinc cation (Zn 2+ ), cadmium cation (Cd 2+ ), germanium cation (Ge 2+ ), tin cation (Sn 2+ ) and lead cation (Pb 2+ ) at least one selected from <7> The composite material according to claim 1, <9> The perovskite nanoparticles are at least one compound selected from methylammonium lead chloride (MAPbCl3), methylammonium lead bromide (MAPbBr3) and methylammonium lead iodide (MAPbI3). <1> ~ <8> 2. The composite material according to claim 1 . <10> At least a portion of the ligands are a molecule having at least one polar functional group selected from a carboxyl group that does not deprotonate, an amino group that does not protonate, a ketone group, and a phosphine oxide group; A molecule having at least one ionic functional group selected from a deprotonated carboxyl group, a protonated amino group, a quaternary ammonium group, a sulfate group, a sulfonate group, a phosphate group, and a thiol group; and Cations and anions derived from at least one ionic compound selected from halides, acetates, nitrates, sulfates, and tetrafluoroborates. At least one selected from <1> ~ <9> 2. The composite material according to claim 1 . <11> The layered oxide structure is an oxide containing at least one atom selected from silicon, boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, zinc, molybdenum, tungsten, niobium, and tantalum, The layered oxide structure is an oxide containing silicon atoms, At least a portion of the layered oxide structure is a silicon oxide; The halide anion is at least one selected from a chloride anion, a bromide anion, and an iodide anion; At least a portion of the cations A is at least one selected from the group consisting of methylammonium cations, formamidinium cations, and cesium cations; At least a portion of the cations B are main group metal cations; The typical metal cation is the magnesium cation (Mg 2+ ), calcium cation (Ca2+ ), strontium cation (Sr 2+ ), barium cation (Ba 2+ ), zinc cation (Zn 2+ ), cadmium cation (Cd 2+ ), germanium cation (Ge 2+ ), tin cation (Sn 2+ ) and lead cation (Pb 2+ ) at least one selected from The perovskite nanoparticles are at least one compound selected from methylammonium lead chloride (MAPbCl3), methylammonium lead bromide (MAPbBr3) and methylammonium lead iodide (MAPbI3); At least a portion of the ligands are a molecule having at least one polar functional group selected from a carboxyl group that does not deprotonate, an amino group that does not protonate, a ketone group, and a phosphine oxide group; A molecule having at least one ionic functional group selected from a deprotonated carboxyl group, a protonated amino group, a quaternary ammonium group, a sulfate group, a sulfonate group, a phosphate group, and a thiol group; and Cations and anions derived from at least one ionic compound selected from halides, acetates, nitrates, sulfates, and tetrafluoroborates. At least one selected from <1> The composite material according to claim 1, <12> A first step of mixing a layered oxide containing at least one metal ion selected from alkali metals and alkaline earth metals with a source of divalent cation B in an aqueous solvent to obtain a layered oxide in which at least a portion of the metal ions in the layered oxide are ion-exchanged with cation B; A second step of mixing the layered oxide obtained in the first step, a source of monovalent cation A and monovalent anion X, and a source of ligand in an organic solvent to obtain a composite material containing perovskite-type nanoparticles having a composition represented by the general formula ABX3 and ligands in a layered oxide structure derived from the layered oxide; A method for manufacturing a composite material comprising: Here, at least a portion of the anions X are halide anions. <13> The oxide sheet in the layered oxide subjected to the mixing in the first step is an oxide containing at least one atom selected from silicon, boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, zinc, molybdenum, tungsten, niobium and tantalum. <12> The manufacturing method described in <14> The oxide sheet in the layered oxide subjected to the mixing in the first step is an oxide containing silicon atoms. <13> The manufacturing method described in <15> The layered oxide subjected to mixing in the first step is at least one selected from Kenyaite, Magadiite, and potassium hydrogen disilicate; <14> The manufacturing method described in <16> The halide anion is at least one selected from a chloride anion, a bromide anion, and an iodide anion; <12> ~ <15> The method for producing a product according to any one of claims 1 to 5. <17> At least a portion of the cations A is at least one selected from the group consisting of methylammonium cations, formamidinium cations and cesium cations; <12> ~ <16> The method for producing a product according to any one of claims 1 to 5. <18> At least a portion of the cations B are main group metal cations; <12> ~ <17> The method for producing a product according to any one of claims 1 to 5. <19> The typical metal cation is the magnesium cation (Mg 2+ ), calcium cation (Ca 2+ ), strontium cation (Sr 2+ ), barium cation (Ba 2+ ), zinc cation (Zn 2+ ), cadmium cation (Cd 2+ ), germanium cation (Ge 2+ ), tin cation (Sn 2+ ) and lead cation (Pb 2+) at least one selected from <18> The manufacturing method described in <20> obtaining a composite material comprising, as perovskite nanoparticles, at least one compound selected from methylammonium lead chloride (MAPbCl3), methylammonium lead bromide (MAPbBr3) and methylammonium lead iodide (MAPbI3); <12> ~ <19> The method for producing a product according to any one of claims 1 to 5. <21> At least a portion of the source of the ligand is a molecule having at least one polar functional group selected from a carboxyl group that does not deprotonate, an amino group that does not protonate, a ketone group, and a phosphine oxide group; A molecule having at least one ionic functional group selected from a carboxyl group that is deprotonated in an organic solvent, an amino group that is protonated in an organic solvent, a quaternary ammonium group, a sulfate group, a sulfonic acid group, a phosphate group, and a thiol group; and At least one ionic compound selected from the group consisting of halide salts, acetate salts, nitrate salts, sulfate salts, and tetrafluoroborate salts. At least one selected from <12> ~ <20> The method for producing a product according to any one of claims 1 to 5. Effect of the Invention

[0013] According to the composite material of the present invention, a new composite material containing perovskite nanoparticles using a material that replaces organic polymers as a matrix can be provided.

[0014] In addition, the manufacturing method of the present invention makes it possible to manufacture the above-mentioned new composite material. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 shows data of powder X-ray diffraction measurements for the solids obtained in Examples 1 to 5. [Diagram 2] FIG. 2 shows data of ultraviolet-visible diffuse reflectance spectrum measurement for the solids obtained in Examples 1 to 3. [Diagram 3] FIG. 3 shows the data of fluorescence spectrum measurement (excitation wavelength 365 nm) for the solids obtained in Examples 1 and 2. [Figure 4] FIG. 4 is a transmission electron microscope image of the solid obtained in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Composite materials> The composite material of the present invention is a composite material containing perovskite nanoparticles having a composition represented by the general formula ABX3 and a ligand in a layered oxide structure, where A represents one or more monovalent cations, B represents one or more divalent cations, and X represents one or more monovalent anions, and at least a part of the anions X is a halide anion. The composite material of the present invention is a novel material containing perovskite nanoparticles and a ligand in a layered oxide structure as an inorganic material matrix.

[0017] The layered oxide structure is a structure in which oxides (oxide sheets) having a two-dimensionally expanding structure are laminated. The layered oxide structure is a structure that forms the skeleton of the layered oxide prepared as a raw material in the manufacturing method of the composite material described later. Since the layered oxide structure is the skeleton part of the layered oxide remaining through the processing in the manufacturing method described later, it can also be said to be a residual structure derived from the layered oxide prepared as a raw material. The layered oxide structure does not need to be completely identical to the structure in the layered oxide before processing. For example, as described later, the layered oxide contains alkali metal ions or alkaline earth metal ions in the interlayer space (space between oxide sheets) of the layered structure, but the amount of alkali metal ions or alkaline earth metal ions present in the interlayer space of the composite material of the present invention is thought to be reduced compared to the initial amount by ion exchange described later. Furthermore, perovskite-type nanoparticles are generated in the interlayer space of the composite material of the present invention. In this way, due to the change of ion species by ion exchange and the generation of nanoparticles, the local charging state of the interlayer space and the interlayer distance may change.

[0018] The layered oxide structure is not limited as long as it allows the generation of perovskite nanoparticles in the structure. The layered oxide structure is preferably a layered structure of oxide containing at least one atom selected from silicon, boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, zinc, molybdenum, tungsten, niobium, and tantalum. The above-mentioned oxides are particularly stable and have low reactivity with perovskite nanoparticles, so that they have little effect on the nucleation of perovskite nanoparticles. From the viewpoint of the stability of the layered oxide structure, the layered oxide structure is preferably a layered structure of oxide containing silicon atoms, and more preferably silicon oxide. In addition, the layered oxide structure may be an oxide containing silicon atoms and at least one atom selected from boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, and zinc. Silicon oxide has a structure in which four oxygen atoms are coordinated around silicon. Boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium and zinc are also atoms capable of four-coordination with oxygen atoms, like silicon atoms. Therefore, oxides containing silicon atoms and these atoms also have high stability as layered oxide structures. The layered oxide structures may be used alone or in a mixture of two or more types. When the layered oxide structure is a mixture of two or more types, it is preferable that at least a part of the layered oxide structure is silicon oxide. The layered oxide structure can be identified, for example, by X-ray diffraction measurement.

[0019] The perovskite nanoparticles and ligands in the composite material of the present invention are believed to be mainly dispersed in the interlayer spaces (spaces between oxide sheets) in the layered oxide structure. It has been reported that some of the oxygen atoms close to the interlayer spaces in the layered oxide structure are negatively charged, whereas the perovskite nanoparticles as a whole are positively charged. It is believed that the balance between the negative charges in the interlayer spaces and the positive charges of the nanoparticles contributes to the stability of the perovskite nanoparticles in their dispersed state.

[0020] Perovskite nanoparticles are nano-sized crystal particles of a perovskite metal halide compound having a composition represented by the general formula ABX3. The particle size of the nanoparticles is, for example, 0.5 to 20 nm, and can be 1 to 15 nm or 2 to 10 nm.

[0021] A represents one or more monovalent cations, and is not particularly limited. Examples of the monovalent cations include nitrogen-containing organic compound cations and alkali metal cations. Examples of the nitrogen-containing organic compound cations include ammonium cation (NH + ), alkylammonium cations with carbon atoms of 6 or less, formamidinium cations (HC(NH2)2 + ), guanidinium cation (C(NH2)3 + ), imidazolium cation, pyridinium cation and pyrrolidinium cation. Examples of alkali metal cations include lithium cation (Li + ), sodium cation (Na + ), potassium cation (K + ), rubidium cation (Rb + ) and the cesium cation (Cs + ) are examples of these cations. These cations have a small ionic diameter and are easily accommodated within the lattice of the perovskite crystal, making it easier for the perovskite nanoparticles to form stable crystals. A preferred example of an alkylammonium cation having 6 or less carbon atoms is the methylammonium cation (CH3NH3 + ), ethylammonium cation (C2H5NH3 + ) and propylammonium cation (C3H7NH3 + ) are included. These cations may be used alone or in combination of two or more. From the viewpoint of easily obtaining high luminous efficiency, at least a part of the A cations is preferably at least one selected from the group consisting of methylammonium cations, formamidinium cations and cesium cations, more preferably methylammonium cations, and the A cations may be only methylammonium cations.

[0022] B represents one or more divalent cations, and is not particularly limited. Examples of the divalent cation include divalent transition metal cations (metals of groups 3 to 11) and divalent typical metal cations (metals other than transition metals). Examples of the divalent transition metal cation include scandium cation (Sc 2+ ), titanium cation (Ti 2+ ), vanadium cation (V 2+ ), chromium cation (Cr 2+ ), manganese cation (Mn 2+ ), iron cation (Fe 2+ ), cobalt cation (Co 2+ ), nickel cation (Ni 2+ ), copper cation (Cu 2+ ), palladium cation (Pd 2+ ), europium cation (Eu 2+ ) and ytterbium cation (Yb 2+ ) As a divalent typical metal cation, for example, magnesium cation (Mg 2+ ), calcium cation (Ca 2+ ), strontium cation (Sr 2+ ), barium cation (Ba 2+ ), zinc cation (Zn 2+ ), cadmium cation (Cd 2+ ), germanium cation (Ge 2+ ), tin cation (Sn 2+ ) and lead cation (Pb 2+ ) can be mentioned. These cations may be used alone or in combination of two or more. From the viewpoint of easily forming stable crystals of the perovskite nanoparticles, at least a part of the B cation is preferably at least one selected from typical metal cations, more preferably at least one selected from tin cations and lead cations. Furthermore, from the viewpoint of easily obtaining strong luminescence, it is particularly preferable that the B cation is a lead cation.

[0023] X represents one or more monovalent anions, at least a part of which is a halide anion, and is not particularly limited. Examples of the halide anion include a fluoride anion (F - ), chloride anion (Cl - ), bromide anion (Br - ) and iodide anion (I - ). The halide anion may be used alone or in combination of two or more kinds. The emission of the nanoparticles can be controlled to a desired wavelength depending on the combination of anion species and their ratio. From the viewpoint that the perovskite nanoparticles are likely to form stable crystals and to easily obtain strong emission in the visible light range, the halide anion is preferably at least one selected from chloride anion, bromide anion, and iodide anion. The emission color is blue when chloride anion is used, green when bromide anion is used, and red when iodide anion is used. When chloride anion, bromide anion, iodide anion, or a mixture thereof is used, it is possible to obtain a desired emission spectrum in almost the entire visible light range while maintaining a narrow full width at half maximum of the emission spectrum. The X anion can contain a monovalent anion other than a halide anion. As a monovalent anion other than a halide anion, for example, a cyanide anion (CN - ), thiocyanate anion (SCN - ), isothiocyanate anion (CNS - ) and other pseudohalide anions.

[0024] The perovskite nanoparticles are preferably compounds in which the A cation is at least one selected from methylammonium cations, formamidinium cations and cesium cations, the B cation is at least one selected from tin cations and lead cations, and the X anion is at least one selected from chloride anions, bromide anions and iodide anions, and are particularly preferably at least one compound selected from methylammonium lead chloride (MAPbCl3), methylammonium lead bromide (MAPbBr3) and methylammonium lead iodide (MAPbI3).

[0025] The ligand is a molecule derived from a ligand material used as a ligand supply source in the method for producing a composite material described later. The ligand is, for example, the ligand material itself, which is a molecule having a polar functional group, a molecule having an ionic functional group generated by protonating or deprotonating the ligand material in a solvent, or a cationic molecule, an anionic molecule, or a halide anion generated by dissociating the ligand material, which is an ionic compound, into ions in a solvent. At least a part of the ligand is preferably a molecule having at least one polar functional group selected from a non-deprotonated carboxyl group, a non-protonated amino group, a ketone group, and a phosphine oxide group, a molecule having at least one ionic functional group selected from a deprotonated carboxyl group, a protonated amino group, a quaternary ammonium group, a sulfate group, a sulfonic acid group, a phosphate group, and a thiol group, and at least one selected from a cationic molecule, an anionic molecule, and a halide anion. The ligand may be either a cationic ligand or an anionic ligand, but it is preferable to include both a cationic ligand and an anionic ligand. This is to act on both the cationic and anionic sites exposed in the perovskite nanoparticles. In particular, the ligand preferably contains at least one selected from a molecule having a deprotonated carboxyl group (anionic ligand) and a molecule having a protonated amino group (cationic ligand), and more preferably contains both of them. Examples of molecules having a deprotonated carboxyl group include deprotonated oleic acid, stearic acid, palmitic acid, linoleic acid, and arachidic acid. Examples of molecules having a protonated amino group include protonated dodecylamine, oleylamine, hexadecylamine, and octadecylamine. The ligand can be coordinated to the perovskite nanoparticles due to its ionicity or polarity, and is considered to play a role in suppressing the bonding between the nanoparticles. The ligand material will be described later.

[0026] Since a layered oxide structure formed from inorganic materials has superior durability to moisture and light in the atmosphere compared to polymer materials, the composite material of the present invention is expected to exhibit superior stability compared to conventional materials.

[0027] <Method of manufacturing composite materials> Next, a method for producing the above-mentioned composite material will be described. The method for producing a composite material of the present invention comprises the steps of: A first step of mixing a layered oxide containing at least one metal ion selected from alkali metals and alkaline earth metals with a source of divalent cation B in an aqueous solvent to obtain a layered oxide in which at least a portion of the metal ions in the layered oxide are ion-exchanged with cation B; A second step of mixing the layered oxide obtained in the first step, a source of monovalent cation A and monovalent anion X, and a source of ligand in an organic solvent to obtain a composite material containing perovskite-type nanoparticles having a composition represented by the general formula ABX3 and ligands in a layered oxide structure derived from the layered oxide; where at least a portion of the anions X are halide anions.

[0028] The layered oxide to be mixed in the first step is a layered compound having a layered oxide structure as a skeleton and containing at least one metal ion of an alkali metal and an alkaline earth metal in the interlayer space. This layered oxide has an ion exchange ability by containing at least one metal ion of an alkali metal and an alkaline earth metal. As a result, when the layered oxide is mixed with a source of a divalent cation B in an aqueous solvent, at least a part of the metal ions in the layered oxide are ion-exchanged with the cation B. The layered oxide may contain hydrogen ions as cations in addition to the above metal ions.

[0029] The oxide sheet in the layered oxide is preferably an oxide containing at least one atom selected from silicon, boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, zinc, molybdenum, tungsten, niobium, and tantalum. The above-mentioned oxides are particularly stable and have low reactivity with perovskite nanoparticles, so that they have little effect on the nucleation of perovskite nanoparticles. In terms of the stability and ion exchange capacity of the layered oxide structure, the oxide sheet of the layered oxide is preferably an oxide containing silicon atoms. The oxide sheet of the layered oxide is silicon oxide, that is, the layered oxide may be a silicate. The oxide sheet of the layered oxide may be an oxide containing silicon atoms and at least one atom selected from boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, and zinc. Silicon oxide has a structure in which four oxygen atoms are coordinated around silicon. Boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium and zinc are also atoms capable of four-coordination with oxygen atoms, like silicon atoms, and it is known that layered oxides including silicon atoms and oxide sheets containing these atoms also have ion exchange ability. Therefore, oxides in which part of the silicon in silicon oxide is replaced with the above-mentioned atoms can also be used as layered oxides in the manufacturing method of the present invention. The layered oxide may be used alone or in a mixture of two or more kinds. When the layered oxide is a mixture of two or more kinds, it is preferable that at least a part of the layered oxide is a silicate.

[0030] The alkali metal is preferably at least one selected from lithium (Li), sodium (Na), and potassium (K), and more preferably at least one selected from sodium and potassium. The alkaline earth metal is preferably at least one selected from magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba), and more preferably at least one selected from magnesium and calcium. In particular, from the viewpoints of the stability of the layered oxide structure and the ion exchange ability, the metal ions in the layered oxide are preferably alkali metals, more preferably at least one selected from lithium, sodium, and potassium, and even more preferably at least one selected from sodium and potassium.

[0031] Examples of the layered oxide used for the mixing in the first step include various silicates, titanates, and clay minerals. In particular, from the viewpoints of the stability of the layered oxide structure and the ion exchange ability, the layered oxide is preferably a layered oxide containing at least one metal ion of an alkali metal and an alkaline earth metal in the interlayer space and having a layered skeleton containing silicon atoms, and more preferably a layered silicate containing at least one metal ion of an alkali metal and an alkaline earth metal in the interlayer space. The layered silicate is not particularly limited, but M 2 / n O·xSiO2·yH2O (M represents a cation component composed of at least one metal ion of an alkali metal and an alkaline earth metal and a hydrogen ion of an optional component, n represents the average valence of the cation M, and x and y satisfy 2 < x < 40 and 1 < y < 20), and is preferably a silicate compound having such a composition. The cation M in the layered silicate preferably contains an alkali metal ion, and more preferably contains at least one selected from sodium and potassium. The layered silicate is, for example, kenyaite (Na2Si 22 O 45 ·10H2O), magadiite (Na2Si 14 O 29 ·10H2O), octosilicate (Na2Si32 O 64 More preferably, it is potassium hydrogen silicate (KHSi2O5).

[0032] The layered oxide may be a single bulk body, but is preferably in the form of particles of about 1 to 5 μm, which increases the contact area between the layered oxide and the aqueous solvent and makes it easier to promote the reaction.

[0033] The source of cation B is not limited as long as it can supply cation B. Examples of the source of cation B include compounds containing divalent transition metal cations and compounds containing divalent typical metal cations. These compounds may be used alone or in combination of two or more. The source of cation B is preferably at least one selected from acetates, carboxylates other than acetates, carbonates, nitrates, sulfates, and halides containing the above-mentioned transition metal cations or typical metal cations, more preferably at least one selected from acetates and carboxylates other than acetates, and particularly preferably acetates. The compound salt may be an anhydride or a hydrate. In particular, the source of cation B is preferably at least one selected from acetates, carboxylates other than acetates, carbonates, nitrates, sulfates, and halides containing lead cations, more preferably at least one selected from acetates containing lead cations and carboxylates other than acetates, and particularly preferably acetates containing lead cations.

[0034] The amount of the source of cation B can be appropriately adjusted depending on the type of each source and the layered oxide. The amount of the source of cation B can be, for example, 1 to 1000 parts by mass, 3 to 900 parts by mass, or 5 to 300 parts by mass per 100 parts by mass of the layered oxide.

[0035] The aqueous solvent is not particularly limited, and is typically water, and may contain a small amount of organic solvent as necessary. The amount of the aqueous solvent is not particularly limited, and is preferably a sufficient amount so that the entire solid material is immersed in the aqueous solvent.

[0036] In the first step, the layered oxide and a source of divalent cation B are mixed in an aqueous solvent to obtain a layered oxide in which the metal ions in the layered oxide are ion-exchanged with cation B. The temperature of the aqueous solvent during mixing is, for example, 0 to 90°C, preferably 40 to 80°C, and may be 50 to 70°C. It is preferable to thoroughly stir the mixture during mixing. The stirring time is not limited, but is, for example, 5 to 40 hours, preferably 10 to 30 hours, and may be 15 to 25 hours. The mixing may be performed in an autoclave. When the layered oxide and a source of divalent cation B are mixed in an aqueous solvent, ion exchange between the metal ions in the layered oxide and cation B occurs in the aqueous solvent, and an ion-exchanged layered oxide is obtained. After the first step, the obtained solid may be washed with pure water and dried as appropriate.

[0037] The source of monovalent cation A and monovalent anion X in the second step is not limited as long as it can supply cation A and anion X. This supply source may be a mixture of a material supplying cation A and a material supplying anion X. In other words, cation A and anion X may be supplied from different compounds, or may be supplied from a single compound. In order to perform the second step more simply, at least a part of the source of cation A and anion X is preferably a single compound that supplies both cation A and anion X, and the source of cation A and anion X may be a single compound that supplies both cation A and anion X. Examples of compounds that supply both cation A and anion X include compound salts consisting of the above-mentioned cation A and the above-mentioned anion X. Examples of such compound salts include halogenated nitrogen-containing organic compounds and alkali metal halides. Examples of halogenated nitrogen-containing organic compounds include ammonium halides, quaternary ammonium halides (such as methylammonium halides), formamidinium halides, and guanidinium halides. Examples of the alkali metal halide include rubidium halide and cesium halide. These compounds may be used alone or in combination of two or more. The source of the cation A and the anion X preferably includes at least one selected from the group consisting of cesium halide and quaternary ammonium halide, and more preferably includes quaternary ammonium halide (particularly, methylammonium halide).

[0038] The amount of the source of cation A and anion X can be appropriately adjusted depending on the type of each source and the layered oxide. The amount of the source of cation A and anion X can be, for example, 1 to 1000 parts by mass, 5 to 500 parts by mass, or 10 to 200 parts by mass per 100 parts by mass of the layered oxide obtained in the first step. When the source of cation A and anion X is a mixture of a material that supplies cation A and a material that supplies anion X, it is preferable that the supply amount of each material is within the above range, and it is preferable that the total amount of the mixture is within the above range.

[0039] The ligand source is not limited, and any known ligand material capable of supplying a ligand usable for surface treatment of perovskite nanoparticles can be used. The ligand source is, for example, a molecule having a polar functional group, a molecule having a functional group exhibiting ionicity in a solvent, and an ionic compound dissociating into ions in a solvent. The ligand source may be used alone or in combination of two or more. At least a part of the ligand source is preferably selected from a molecule having at least one polar functional group selected from a carboxyl group that is not deprotonated, an amino group that is not protonated, a ketone group, and a phosphine oxide group, a carboxyl group that is deprotonated in an organic solvent, an amino group that is protonated in an organic solvent, a molecule having at least one ionic functional group selected from a quaternary ammonium group, a sulfate group, a sulfonic acid group, a phosphoric acid group, and a thiol group, and at least one ionic compound selected from a halide salt, an acetate salt, a nitrate salt, a sulfate salt, and a tetrafluoroborate salt.

[0040] In particular, the ligand source preferably includes at least one selected from a molecule having a carboxyl group that deprotonates in a solvent, a molecule having an amino group that protonates in a solvent, a quaternary ammonium halide, and an amino acid. Furthermore, the ligand source more preferably includes at least one selected from a molecule having a carboxyl group that deprotonates in a solvent (anionic ligand) and a molecule having an amino group that protonates in a solvent (cationic ligand), and particularly preferably includes both of these. Examples of molecules having a carboxyl group that deprotonates in a solvent include oleic acid, stearic acid, palmitic acid, linoleic acid, and arachidic acid. Examples of molecules having an amino group that protonates in a solvent include dodecylamine, oleylamine, hexadecylamine, and octadecylamine.

[0041] The amount of the ligand source can be appropriately adjusted depending on the type of each source and the layered oxide. The amount of the ligand source is, for example, 1 to 1000 mL, 10 to 500 mL, or 50 to 200 mL per 1000 mL of the organic solvent in the second step. The volume ratio of the amount of the anionic ligand source to the amount of the cationic ligand source is, for example, 0.01 to 100, 0.5 to 50, or 1 to 20.

[0042] The organic solvent is not particularly limited and is appropriately selected from known organic solvents depending on the source and the type of layered oxide. Examples of the organic solvent include 1-butanol, isobutanol, 1-propanol, isopropanol, and toluene. The amount of the organic solvent is not particularly limited and is preferably sufficient to immerse the entire solid material in the organic solvent.

[0043] In the second step, the layered oxide obtained in the first step, a source of monovalent cation A and monovalent anion X, and a source of ligand are mixed in an organic solvent to obtain a composite material containing perovskite nanoparticles having a composition represented by the general formula ABX3 and a ligand in a layered oxide structure derived from the layered oxide. The temperature of the organic solvent during mixing is, for example, 0 to 120°C, preferably 10 to 80°C, and may be 15 to 40°C. It is preferable to stir well during mixing. The stirring time is not limited, but is, for example, 5 to 100 minutes, preferably 10 to 80 minutes, and may be 15 to 60 minutes. When the layered oxide obtained in the first step, a source of monovalent cation A and monovalent anion X, and a source of ligand are mixed in an organic solvent, perovskite nanoparticles are generated in the layered oxide structure, and a composite material in which the nanoparticles are dispersed in the layered oxide structure is obtained. At this time, it is considered that the ligand is coordinated to the nanoparticles. After the second step, the obtained solid may be washed with an organic solvent and dried as appropriate.

[0044] The above-described manufacturing method makes it possible to disperse nanoparticles in an inorganic material matrix.

[0045] The manufacturing method of the present invention also has the effect of dispersing nanoparticles in a matrix at a higher density than conventional methods. As will be described in detail in the Examples, the manufacturing method of the present invention can disperse nanoparticles at a density of about 10,000 particles / μm 2 Nanoparticles can be dispersed in a matrix (layered oxide structure) at a density of about 200 particles / μm. For example, Non-Patent Document 1 shows a TEM image showing nanoparticles dispersed in a polymer matrix, along with a scale bar, and the density of nanoparticles estimated from this image is about 200 particles / μm. 2 This result shows that the composite material of the present invention is superior to conventional materials in terms of physical properties such as light emission characteristics and wavelength conversion characteristics.

[0046] In addition, according to the manufacturing method of the present invention, three operations that would normally be independent steps, namely, synthesis of nanoparticles, preparation of nanoparticles by ligand treatment, and dispersion of nanoparticles in a matrix, can be realized in one mixing operation (the second step). Therefore, the manufacturing method of the present invention may be able to manufacture composite materials with simpler operations than conventional methods, and is expected to be a method suitable for mass production of composite materials. EXAMPLES

[0047] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.

[0048] <Example 1> Kenyaite was used as the layered oxide. 0.98 g of lead acetate trihydrate (cation B: lead cation Pb 2+ Kenyaite was immersed in an aqueous solution obtained by dissolving lead cations (source of lead) in 20 mL of pure water, and the aqueous solution was stirred at 60°C for one day to obtain Kenyaite with lead cations introduced by ion exchange. The solid obtained was washed with pure water and dried at 50°C for 24 hours. 5 mg of methylammonium chloride (cation A: methylammonium cation CH3NH3 +and anion X: chloride anion Cl - 0.1 g of the dried solid was immersed in an organic solution obtained by dissolving 0.1 mL of methylammonium lead chloride (MAPbCl3) (source of anionic ligand), 0.1 mL of oleic acid (source of anionic ligand), and 0.01 mL of oleylamine (source of cationic ligand) in 1 mL of 1-butanol, and the organic solution was stirred at 25 °C for 30 min to obtain a composite material containing perovskite-type nanoparticles of methylammonium lead chloride (MAPbCl3) and ligands in a layered oxide structure derived from Kenyaite. The obtained solid was washed with 1-butanol and dried in vacuum at 30 °C.

[0049] <Example 2> 10 mg of methylammonium bromide was substituted for 5 mg of methylammonium chloride (Cation A: Methylammonium cation CH3NH3 + and anion X: bromide anion Br - The same procedure as in Example 1 was carried out, except that a source of lead bromide (MAPbBr3) was used, to obtain a composite material containing perovskite nanoparticles of methylammonium lead bromide (MAPbBr3) and ligands in a layered oxide structure derived from Kenyaite.

[0050] <Example 3> 10 mg of methylammonium iodide was substituted for 5 mg of methylammonium chloride (Cation A: Methylammonium cation CH3NH3 + and anion X: iodide anion I - A similar process to that of Example 1 was carried out, except that a source of lead iodide (MAPbI3) was used, to obtain a composite material containing perovskite nanoparticles of methylammonium lead iodide (MAPbI3) and ligands in a layered oxide structure derived from Kenyaite.

[0051] <Example 4> Magadiite was used as the layered oxide. 0.5 g of magadiite was immersed in an aqueous solution obtained by dissolving 0.71 g of lead acetate trihydrate in 20 mL of pure water, and the aqueous solution was stirred at 60 °C for one day to obtain magadiite with lead cations introduced by ion exchange. The solid obtained was washed with pure water and dried at 50 °C for 24 h. 0.1 g of the dried solid was immersed in an organic solution obtained by dissolving 10 mg of methylammonium bromide, 0.1 mL of oleic acid, and 0.01 mL of oleylamine in 1 mL of 1-butanol, and the organic solution was stirred at 25 °C for 30 min to obtain a composite material containing MAPbBr3 perovskite-type nanoparticles and ligands in the layered oxide structure derived from magadiite. The solid obtained was washed with 1-butanol and dried in vacuum at 30 °C.

[0052] <Example 5> Potassium hydrogen disilicate was used as the layered oxide. 0.5 g of potassium hydrogen disilicate was immersed in an aqueous solution obtained by dissolving 4.25 g of lead acetate trihydrate in 20 mL of pure water, and the aqueous solution was stirred at 60 °C for 1 day to obtain potassium hydrogen disilicate with lead cations introduced by ion exchange. The solid obtained was washed with pure water and dried at 50 °C for 24 h. 0.1 g of the dried solid was immersed in an organic solution obtained by dissolving 10 mg of methylammonium bromide, 0.1 mL of oleic acid, and 0.01 mL of oleylamine in 1 mL of 1-butanol, and the organic solution was stirred at 25 °C for 30 min to obtain a composite material containing MAPbBr3 perovskite-type nanoparticles and ligands in the layered oxide structure derived from potassium hydrogen disilicate. The solid obtained was washed with 1-butanol and dried in vacuum at 30 °C.

[0053] <Powder X-ray diffraction measurement> Powder X-ray diffraction (XRD) measurements were performed on the solids obtained in Examples 1 to 5. FIG. 1(a) shows XRD data for the solid obtained in Example 1. In FIG. 1(a), the data at the top is for Kenyaite before immersion in an aqueous solution, the data in the center is for Kenyaite with lead cations introduced by ion exchange, and the data at the bottom is for the composite material finally obtained. Comparing the data at the top and the center, a peak change due to a change in the interlayer distance in the layered structure (for example, disappearance of a peak near 3 to 4 degrees and appearance of a peak near 12 to 13 degrees) was confirmed, and it was confirmed that lead cations were introduced into the layered oxide by ion exchange. From the data at the bottom, a diffraction peak derived from the crystal phase of MAPbCl3 was confirmed. From all the data, a peak reflecting the layered structure of the layered oxide (Kenyaite) was confirmed. From the above, it was found that although there was a change in the interlayer distance, the layered structure derived from the layered oxide was maintained in the composite material of the present invention.

[0054] 1(b) and (c) show the XRD data of the solids obtained in Examples 2 and 3, respectively. In Examples 2 and 3, as in Example 1, it was confirmed from the peak change due to the change in the interlayer distance that lead cations were introduced into the layered oxide by ion exchange. Furthermore, the data at the bottom of FIG. 1(b) confirmed a diffraction peak derived from the crystal phase of MAPbBr3, and the data at the bottom of FIG. 1(c) confirmed a diffraction peak derived from the crystal phase of MAPbI3. It was also found from FIGS. 1(b) and (c) that the layered structure derived from the layered oxide was maintained in the composite material of the present invention.

[0055] Fig. 1(d) shows XRD data of the solids obtained in Example 4 (top) and Example 5 (bottom). From these data, it was confirmed that a MAPbBr3 crystal phase was formed in the layered oxide structure derived from magadiite in Example 4, and that MAPbBr3 crystals were formed in the layered oxide structure derived from potassium hydrogen disilicate in Example 5. In Examples 4 and 5, the layered structure derived from the layered oxide was maintained in the composite material of the present invention.

[0056] <UV-Visible Diffuse Reflectance Spectrum Measurement> The UV-visible diffuse reflectance spectra of the solids obtained in Examples 1 to 3 were measured. Figure 2 shows the measurement results. The band gap of each crystal was calculated from the wavelength at which the slope of the diffuse reflectance spectrum changed significantly. The band gaps of the solids obtained in Examples 1 to 3 were 2.95 eV, 2.23 eV, and 1.57 eV, respectively, which were almost the same as the band gap of methylammonium lead halide.

[0057] <Fluorescence spectrum measurement> The fluorescence spectra of the solids obtained in Examples 1 and 2 were measured using an excitation wavelength of 365 nm. The measurement results are shown in Figure 3. Emissions (half width of about 29 nm) centered at wavelengths of 413 nm and 525 nm were confirmed for Examples 1 and 2, respectively.

[0058] <Transmission electron microscope observation> The nanostructure of the solid obtained in Example 2 was observed using a transmission electron microscope (TEM). Figure 4 shows the TEM image. It was confirmed that nanoparticles with an average particle size of about 3 nm were dispersed in the layered oxide structure derived from the layered oxide. From this image, the particle density was about 10,000 particles / μm 2 It was. Perovskite nanoparticles are very unstable due to their strong ionicity, and when they are densely assembled, the particles often bond to each other and lose their luminescence properties. The reason why the nanoparticles are dispersed even at such a high density as described above and the composite material shows luminescence properties as shown in Figure 3 is thought to be because the ligands function as spacers between the nanoparticles. In addition, the layered oxide structure derived from the layered oxide is thought to contribute to the stabilization of the nanoparticles in the dispersed state. It has been reported that some of the oxygen atoms close to the interlayer space in the layered oxide structure are negatively charged, while perovskite nanoparticles are positively charged as a whole. It can be assumed that a charge balance is formed by the negative charge in the interlayer space and the positive charge of the nanoparticles. [Industrial Applicability]

[0059] The composite material of the present invention can be applied to, for example, a wavelength converting material composition and a wavelength converting member using the composition. Furthermore, the composite material is expected to be applicable to security inks that utilize a fluorescent response due to a specific wavelength, electronic devices (such as electroluminescent elements), optical devices (such as backlight units and optical switches), and energy conversion devices (such as solar cells and photodetectors).

Claims

1. General formula ABX 3 A composite material comprising perovskite nanoparticles and ligands in a layered oxide structure, the composite having a composition represented by the formula: Here, A represents one or more monovalent cations, B represents one or more divalent cations, X represents one or more monovalent anions, and at least a portion of the anions X are halide anions.

2. 2. The composite material according to claim 1, wherein the layered oxide structure is an oxide containing at least one atom selected from silicon, boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, zinc, molybdenum, tungsten, niobium, and tantalum.

3. The composite material according to claim 2 , wherein the layered oxide structure is an oxide containing silicon atoms.

4. 4. The composite material of claim 3, wherein at least a portion of the layered oxide structure is silicon oxide.

5. 5. The composite material according to claim 1, wherein the halide anion is at least one selected from the group consisting of chloride anion, bromide anion and iodide anion.

6. 5. The composite material according to claim 1, wherein at least a portion of the cations A is at least one selected from the group consisting of methylammonium cations, formamidinium cations and cesium cations.

7. 5. The composite material according to claim 1, wherein at least a portion of the cations B are main group metal cations.

8. Typical metal cations include magnesium cations (Mg 2+ ), calcium cation (Ca 2+ ), strontium cation (Sr 2+ ), barium cation (Ba 2+ ), zinc cation (Zn 2+ ), cadmium cation (Cd 2+ ), germanium cation (Ge 2+ ), tin cation (Sn 2+ ) and lead cation (Pb 2+ 8. The composite material according to claim 7, wherein the at least one selected from the group consisting of fluororesin, fluorosulfuric acid, fluoroisotope ... and fluoroisotope.

9. Perovskite nanoparticles are made of methylammonium lead chloride (MAPbCl 3 ), methylammonium lead bromide (MAPbBr 3 ) and methylammonium lead iodide (MAPbI 3 5. The composite material according to claim 1, wherein the at least one compound is selected from the group consisting of aryl, aryloxy ...

10. At least a portion of the ligands are a molecule having at least one polar functional group selected from a carboxyl group that does not deprotonate, an amino group that does not protonate, a ketone group, and a phosphine oxide group; A molecule having at least one ionic functional group selected from a deprotonated carboxyl group, a protonated amino group, a quaternary ammonium group, a sulfate group, a sulfonate group, a phosphate group, and a thiol group; and Cations and anions derived from at least one ionic compound selected from halide salts, acetate salts, nitrate salts, sulfate salts, and tetrafluoroborate salts. The composite material according to any one of claims 1 to 4, which is at least one selected from the following:

11. The layered oxide structure is an oxide containing at least one atom selected from silicon, boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, zinc, molybdenum, tungsten, niobium, and tantalum; The layered oxide structure is an oxide containing silicon atoms, At least a portion of the layered oxide structure is a silicon oxide; The halide anion is at least one selected from a chloride anion, a bromide anion, and an iodide anion; At least a portion of the cations A is at least one selected from the group consisting of methylammonium cations, formamidinium cations, and cesium cations; At least a portion of the cations B are main group metal cations; Typical metal cations include magnesium cations (Mg 2+ ), calcium cation (Ca 2+ ), strontium cation (Sr 2+ ), barium cation (Ba 2+ ), zinc cation (Zn 2+ ), cadmium cation (Cd 2+ ), germanium cation (Ge 2+ ), tin cation (Sn 2+ ) and lead cation (Pb 2+ At least one selected from Perovskite nanoparticles are made of methylammonium lead chloride (MAPbCl 3 ), methylammonium lead bromide (MAPbBr 3 ) and methylammonium lead iodide (MAPbI 3 At least one compound selected from At least a portion of the ligands are a molecule having at least one polar functional group selected from a non-deprotonated carboxyl group, a non-protonated amino group, a ketone group, and a phosphine oxide group; A molecule having at least one ionic functional group selected from a deprotonated carboxyl group, a protonated amino group, a quaternary ammonium group, a sulfate group, a sulfonate group, a phosphate group, and a thiol group; and Cations and anions derived from at least one ionic compound selected from halide salts, acetate salts, nitrate salts, sulfate salts, and tetrafluoroborate salts. The composite material according to claim 1 , which is at least one selected from the following:

12. A first step of mixing a layered oxide containing at least one metal ion selected from alkali metals and alkaline earth metals with a source of divalent cation B in an aqueous solvent to obtain a layered oxide in which at least a portion of the metal ions in the layered oxide have been ion-exchanged with cation B; The layered oxide obtained in the first step, a source of monovalent cation A and monovalent anion X, and a source of ligand are mixed in an organic solvent to form a compound of the general formula ABX 3 A second step of obtaining a composite material containing perovskite nanoparticles having a composition represented by the formula: A method for producing a composite material comprising: Here, at least a portion of the anions X are halide anions.

13. The method according to claim 12, wherein the oxide sheet in the layered oxide subjected to the mixing in the first step is an oxide containing at least one atom selected from silicon, boron, aluminum, gallium, iron, chromium, titanium, germanium, tin, zirconium, zinc, molybdenum, tungsten, niobium and tantalum.

14. The method according to claim 13, wherein the oxide sheet in the layered oxide subjected to the mixing in the first step is an oxide containing silicon atoms.

15. The method according to claim 14, wherein the layered oxide subjected to mixing in the first step is at least one selected from the group consisting of kenyaite, magadiite, and potassium hydrogen disilicate.

16. The method according to any one of claims 12 to 15, wherein the halide anion is at least one selected from the group consisting of chloride anion, bromide anion and iodide anion.

17. The method according to any one of claims 12 to 15, wherein at least a portion of the cations A is at least one selected from the group consisting of methylammonium cations, formamidinium cations and cesium cations.

18. The method according to any one of claims 12 to 15, wherein at least a portion of cation B is a typical metal cation.

19. Typical metal cations include magnesium cations (Mg 2+ ), calcium cation (Ca 2+ ), strontium cation (Sr 2+ ), barium cation (Ba 2+ ), zinc cation (Zn 2+ ), cadmium cation (Cd 2+ ), germanium cation (Ge 2+ ), tin cation (Sn 2+ ) and lead cation (Pb 2+ 19. The method according to claim 18, wherein the at least one selected from the group consisting of

20. As perovskite nanoparticles, methylammonium lead chloride (MAPbCl 3 ), methylammonium lead bromide (MAPbBr 3 ) and methylammonium lead iodide (MAPbI 3 The method according to any one of claims 12 to 15, which obtains a composite material comprising at least one compound selected from the group consisting of:

21. At least a portion of the source of the ligand is a molecule having at least one polar functional group selected from a non-deprotonated carboxyl group, a non-protonated amino group, a ketone group, and a phosphine oxide group; A molecule having at least one ionic functional group selected from a carboxyl group that is deprotonated in an organic solvent, an amino group that is protonated in an organic solvent, a quaternary ammonium group, a sulfate group, a sulfonic acid group, a phosphate group, and a thiol group; and At least one ionic compound selected from the group consisting of halide salts, acetate salts, nitrate salts, sulfate salts, and tetrafluoroborate salts. The method according to any one of claims 12 to 15, wherein the at least one selected from the group consisting of

Citation Information

Patent Citations

  • Perovskite / Polymer Composite Light-Emitting Materials, Manufacturing Methods and Applications

    JP2018522959A